A systematic review of the current knowledge regarding revenge pornography and non-consensual sharing of sexually explicit media. (September 2017) - Walker, Kate; Sleath, Emma
Abstract: The aim of this review was to synthesize the current literature regarding revenge pornography and the non-consensual sharing of sexually explicit media. A systematic search was made of five databases using relevant search terms. From these searches, 82 articles were retained for inclusion within the systematic review. The literature spanned areas of research including legal, theory, as well as psychology related empirical papers. The findings show that particularly in the U.S., but in other countries as well, there are significant concerns regarding the implementation of revenge pornography legislation, despite this being recognized as an important endeavor. Non-consensual sharing perpetration and victimization rates can vary considerably according to how the behavior is defined and measured, however, these behaviors were evident for a considerable number of individuals across both genders. Highlights: Non-consensual sharing appears prevalent, although motivations remain unclear. There are significant challenges in developing effective revenge porn legislation. It is unclear if negative effects of cyber-victimization occur for revenge porn victims. There is very little knowledge regarding perpetrators of revenge porn.